Harvest of stones : the German settlement in Renfrew County - Lee-Whiting, Brenda, 1929- (Heritage., 1985)
Driven by Bismarck's wars and by economic hardship, hundreds of people left eastern Germany between 1858 and 1890 to settle in Canada. Using their objects and stories, Lee-Whiting brings to life the culture of a people transplanted to a region that challenged them and met with resilience and resourcefulness.